2003
DOI: 10.1016/s0896-6273(03)00502-6
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Semaphorin-3A Receptor Binding Module

Abstract: The semaphorins are a large group of extracellular proteins involved in a variety of processes during development, including neuronal migration and axon guidance. Their distinctive feature is a conserved 500 amino acid semaphorin domain, a ligand-receptor interaction module also present in plexins and scatter-factor receptors. We report the crystal structure of a secreted 65 kDa form of Semaphorin-3A (Sema3A), containing the full semaphorin domain. Unexpectedly, the semaphorin fold is a variation of the beta p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
164
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(175 citation statements)
references
References 35 publications
10
164
1
Order By: Relevance
“…Second, we found that Sema3A triggered NRP1 oligomerization because NRP1 was redistributed in heavy fractions of the gradients upon ligand binding. Although calculated sedimentation constants are approximate because only partial crystal structure of the protein has been resolved (Antipenko et al, 2003), oligomerization is evident from our results and may possibly be underestimated. This further supports the conclusion that both MAM and TM domain interactions are necessary for the induction of neuropilin signaling, possibly in a concerted manner, because both types of interactions can be effectively antagonized.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Second, we found that Sema3A triggered NRP1 oligomerization because NRP1 was redistributed in heavy fractions of the gradients upon ligand binding. Although calculated sedimentation constants are approximate because only partial crystal structure of the protein has been resolved (Antipenko et al, 2003), oligomerization is evident from our results and may possibly be underestimated. This further supports the conclusion that both MAM and TM domain interactions are necessary for the induction of neuropilin signaling, possibly in a concerted manner, because both types of interactions can be effectively antagonized.…”
Section: Discussionmentioning
confidence: 76%
“…We hypothesized that the biological function of Sema3A was abrogated when interfering with the TM domain because of the destabilization of the receptor complex required for signal transduction. Indeed, it has been proposed that Sema3A dimer (known to be important for binding and collapsing activity; Klostermann et al, 1998;Koppel and Raper, 1998) may undergo a dimer-to-monomer transition upon binding to monomeric NRP1 (Antipenko et al, 2003), a transition that would explain the persistence of binding after destabilization of NRP1 homodimerization. In the other hand, the interference of the TM domain dimerization may be sufficient to generate conformational changes altering optimal binding at the extracellular level.…”
Section: Discussionmentioning
confidence: 99%
“…Known molecular causes of DA are mutations in at least seven genes (TNNI2, TNNT3, TPM2, MYH2, MYH3, MYH8, and MYH13) that encode components of the contractile apparatus of fast-twitch myofibers [Sung et al, 2003a,b;Toydemir et al, 2006a,b]. Since it was shown that Sema3a-signaling controls the timing of motor axon in-growth to the limb and is involved in intramuscular motor reinnervation and restoration of muscle fiber contractile integrity [Antipenko et al, 2003] are shown in green. Residues involved in Plexin binding were deduced from the homologous Sema4D complex [Janssen et al, 2010] and are shown in cyan (stick presentation).…”
Section: Discussionmentioning
confidence: 99%
“…Bidirectional sequencing was performed with vector specific primers (Supplementary Table SIV) and sequencing primers binding within the insert. The crystal structure of murine Sema3a containing the full semaphorin domain (residues 26-520) was retrieved from the PDB databank (PDB code 1Q47) [Antipenko et al, 2003]. The structure of human SEMA3A, which Exhibits 97% sequence identity to murine Sema3a, was generated using SwissModel [Guex and Peitsch, 1997].…”
Section: Materials and Methods Clinical Reportmentioning
confidence: 99%
“…Plexins act as the signal transducing receptors for semaphorins, a family of secreted and cell surface-attached proteins best characterized by their chemorepulsive role in axon guidance (1). The extracellular portions of semaphorins and plexins share a distinctive ␤-propeller fold termed the sema domain (2,3); the plexin cytosolic regions are of unknown structure. Molecules of the MICAL [molecule interacting with CasL (4)] family link signaling from the cytosolic regions of class A plexins to the cytoskeleton (5).…”
mentioning
confidence: 99%